An e-services reference model to streamline the Global Village Grid. (3rd December 2009) - Hashemi, Seyyed Mohsen; Razzazi, Mohammadreza
To realise the Global Village Grid in an e-services framework, software engineers encounter with data and services integration in software developments and implementations. Additionally, unifying the e-services would be realised in global e-governance concerning globalisation trends. Software engineers need some reference architectures to implement an e-services framework in the all-inclusive world. They also need a reference model on which to base their reference architectures. On the other hand, there is no reference model, which could be used to develop and unify e-services. We suggest a reference model called Global Village Grid Reference Model (GVGRM) to realise the Global Village Grid in an e-services framework. Thus, GVGRM could be used as the baseline for any kind of software engineering efforts pertaining to the e-services. Finally, we have used the new definitions to propose the suggested reference model through the suggested ontology called service-oriented strategies and architectures.